Synthesis and Characterization on some Metal Ions of 2-(6-Methoxynaphthalen-2-Yl)Propanoate Complexes - Yousif, Emad; Shneine, Jawad; Ahmed, Ahmed; Salman, Husam (Al-Nahrain Journal of Science, 2013)
A total of five new metal complexes derivatives of 2-(6-methoxynaphthalen-2-yl) propanoate, HL with the metal ions (Cd(II), Zn(II), Sn(II), Ni(II) and Cu(II)) have been successfully prepared in alcoholic medium. The complexes were characterized quantitatively and qualitatively by using micro elemental analysis, FTIR spectroscopy, UV-Vis spectroscopy, magnetic susceptibility and conductivity measurements. From the spectral measurements, monomer structures for the complexes were proposed, square planar geometry was proposed for the copper complex. The other complexes were proposed to be tetrahedral.